KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMA DITINJAU DARI GENDER - Pebianto, Acep; Suhartina, Reyna; Yohana, Ribka; Mustaqimah, Indri A; Hidayat, Wahyu (IKIP Siliwangi, 2018)
This research aims to analyze and examine comparison of critical thinking mathematical ability high school students viewed of gender.. The method in this research is a method of experimentation with the design of the two classes and post-test only. The sample of this research is the grade XI at one high school in the city of Cimahi.. The subject consists of 29 students are male and 43 female students. Research instrument in the form of a test of the ability of critical thinking as much as 4 grains of reserved descriptions and interviews. The analysis of the data used in this research in the form of test t. Research results it gives the conclusion that there was no difference in the ability of critical thinking mathematically high school students viewed of gender